Wieloaspektowość pojęcia konceptualizacja w gramatyce Ronalda Langackera (spojrzenie z perspektywy użytkownika terminologii kognitywnej) - Krystyna Waszakowa (Ksiegarnia Akademicka Publishing, 2020)
Multiaspectuality of the notion of conceptualization in Ronald Langacker’s grammar: from the perspective of a user of cognitive terminology